Development of GOFIN (Google form interactive)-based on the short story worksheet with differentiated learning approach - Khusnul Fatimah; Rima Damayanti; Sri Wahyuni; Dyah Werdiningsih; I. Imrotin (Universitas Muhammadiyah Malang, 2024)
The availability of interactive-based student worksheets that also take into account differences in learning styles is necessary to address the challenges of the digital era in teaching short story writing. This research aims to develop Student Worksheets (LKPD) based on Gofin (Interactive Google Form) for short story text learning with the application of a differentiated approach that is suitable for interests, abilities, and learning styles. This developmental research adapts the ADDIE model and carries out three steps, namely analysis, design, and development. The implementation and evaluation steps are conducted in subsequent research. The research results indicate that this LKPD is highly suitable and engaging with a material validity rate of 87%, media validity of 83%, and student response of 96%. This LKPD is designed to accommodate differences in students' learning styles (kinesthetic, auditory, visual) so that learning objectives can be maximally achieved.